A Shared System of Representation Governing Quantity Discrimination in Canids - Baker, Joseph M.; Morath, Justice; Rodzon, Katrina S.; Jordan, Kerry E. (Frontiers in Psychology, 2012)
One way to investigate the evolution of cognition is to compare the abilities of phylogenetically related species. The domestic dog (Canis lupus familiaris), for example, still shares cognitive abilities with the coyote (C. latrans). Both of these canids possess the ability to make psychophysical “less/more” discriminations of food based on quantity. Like many other species including humans, this ability is mediated by Weber’s Law: discrimination of continuous quantities is dependent on the ratio between the two quantities. As two simultaneously presented quantities of food become more similar, choice of the large or small option becomes random in both dogs and coyotes. It remains unknown, however, whether these closely related species within the same family—one domesticated, and one wild—make such quantitative comparisons with comparable accuracy. Has domestication honed or diminished this quantitative ability? Might different selective and ecological pressures facing coyotes drive them to be more or less able to accurately represent and discriminate food quantity than domesticated dogs? This study is an effort to elucidate this question concerning the evolution of non-verbal quantitative cognition. Here, we tested the quantitative discrimination ability of 16 domesticated dogs. Each animal was given 9 trials in which two different quantities of food were simultaneously displayed to them. The domesticated dogs’ performance on this task was then compared directly to the data from 16 coyotes’ performance on this same task reported by Baker and colleagues (2011).The quantitative discrimination abilities between the two species were strikingly similar. Domesticated dogs demonstrated similar quantitative sensitivity as coyotes, suggesting that domestication may not have significantly altered the psychophysical discrimination abilities of canids. Instead, this study provides further evidence for similar nonverbal quantitative abilities across multiple species.